An investigation into the causes of intraocular inflammation in HIV-positive and HIV-negative patients in the Western Cape Province, South Africa - Smit, Derrick Peter (Stellenbosch: Stellenbosch University, 2018)
Thesis (PhD (Surgical Sciences. Ophthalmology))--Stellenbosch University, 2018.